Function score-based technological trend analysis. (March 2021) - Mun, Changbae; Yoon, Sejun; Raghavan, Nagarajan; Hwang, Dongwook; Basnet, Subarna; Park, Hyunseok
Abstract: This paper proposes a new method to quantitatively evaluate the relative importance of a functionality in a technological domain at a specific time, called function score . Based on the function score and actual demand for each functionality, we developed a framework to analyze dynamic functional trends in a technological domain. To test the proposed method, this paper conducted an empirical study using Genome sequencing technology. The result shows that most of the important functionalities in different periods are well identified by the function score. The trend analysis framework effectively visualizes the dynamic changes of importance and demand for functionalities in Genome sequencing, and the results were also found to be qualitatively acceptable. Therefore, the proposed trend analysis based on the function score is being proposed here as a novel useful for understanding the fundamental developmental trends that occur within a technological domain. Highlights: This research proposes a new method to quantitively evaluate the relative importance of a function in a technological domain, called function score. This research developed a framework for analyzing technological trends based on function scores. The empirical study using Genome sequencing shows that function score-based trend analysis is useful for understanding fundamental developmental trends.